2019
DOI: 10.1097/01.nurse.0000554278.87676.ad
|View full text |Cite
|
Sign up to set email alerts
|

Are genetics/genomics competencies essential for all clinical nurses?

Abstract: In 2006, the American Nurses Association created a set of essential genetics and genomics (G/G) competencies for all RNs, regardless of academic preparation, practice setting, or specialty. However, more than half of the RNs practicing today received no prelicensure education on these G/G competencies. This study describes the current use of G/G nursing competencies in acute care hospitals and how nurses perceive them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…It might also indicate that only a few nurses require extensive insight into genetics to perform their daily work. This assertion seems to be supported by Newcomb et al's inquiry, [22] where a majority of nurses answering a questionnaire said that they never or only very rarely performed many of the competencies deemed essential for all nurses by the American Nurses Association. [10] Nevertheless, a tendency emerging from our analysis was that nurses who had experience working in several different departments seemed to find genetic knowledge more relevant and important for the nursing profession than those who had no prior experience from other fields of nursing care.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It might also indicate that only a few nurses require extensive insight into genetics to perform their daily work. This assertion seems to be supported by Newcomb et al's inquiry, [22] where a majority of nurses answering a questionnaire said that they never or only very rarely performed many of the competencies deemed essential for all nurses by the American Nurses Association. [10] Nevertheless, a tendency emerging from our analysis was that nurses who had experience working in several different departments seemed to find genetic knowledge more relevant and important for the nursing profession than those who had no prior experience from other fields of nursing care.…”
Section: Discussionmentioning
confidence: 95%
“…Taking a global perspective, Calzone et al found that there were genomic literacy deficits in both nursing practice and nursing education in many countries, with only one country out of 19 surveyed having a G/G knowledge and skill requirement for practicing nurses. [21] Recently, the belief that G/G competencies are essential for all registered nurses, regardless of practice setting and medical specialty, has been called into question by Newcomb et al [22] They used a 38-item questionnaire based on the formulated essential competencies [10] to investigate the current use of G/G nursing competencies in acute care hospitals. The aim of the study was both to describe the use of these competencies and to determine whether clinical nurses perceived them as relevant.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries such as the United States, Brazil, and South Africa, the necessity of continuing education for primary healthcare professionals in genetics/genomics is acknowledged because competency in genetics/genomics is difficult to acquire by studying it only during an undergraduate nursing program (Hamilton et al., 2017; Lopes‐Júnior et al., 2017; Newcomb et al., 2019). In Japan, nurse specialists certified in genetics nursing and genetic counselors receive specific genetics/genomics education during graduate school.…”
Section: Discussionmentioning
confidence: 99%
“…Calzone et al (2013) described that competences are well-established, which might reveal why competences were not defined more in the articles. Most TA B L E 3 (Continued) Coleman et al, 2014;Melo et al, 2015;Newcomb et al, 2019;Yeşilçinar et al, 2022).…”
Section: Characteristics Of the Included Studies And Instrumentsmentioning
confidence: 99%
“…In an article concerning the primary healthcare setting, 88.9% of professionals (nurses and physicians) were unfamiliar with the ethical aspects of genetic counselling (Lopes-Júnior et al, 2017). Newcomb et al's (2019) instrument asked nurses about their ability to identify ethical, cultural, legal, ethnic, religious, fiscal and societal issues as a part of genomics in a single question. The results of the question were not presented in their article.…”
Section: Visible Ethicsmentioning
confidence: 99%